Prevalence of common dermatoses in school children of rural areas of Salem; a region of South India - Golfy Jose; Seethalakshmi Ganga Vellaisamy; Nanjappachetty Govindarajan; Kannan Gopalan (Wolters Kluwer Medknow Publications, 2017)
Introduction: Skin diseases are a major health problem in children, which is associated with significant morbidity. Its prevalence ranges from 4.3% to 49.1% in various parts of India in school-based surveys. Objective: The present study was conducted to know the prevalence, epidemiology of various dermatoses, and the factors contributing to those dermatoses among school children of rural areas of Salem. Materials and Methods: A cross-sectional prospective study was conducted in two schools of rural Salem between September 2014 and September 2015. A total of 1000 children between the age group of 5 and 14 years were examined for diseases of the skin and appendages. Data were coded and analyzed. Results: The overall prevalence of skin diseases was 68.2%. Almost 53 types of skin lesions were identified among the students; of these, 15 were infectious, 35 were noninfectious, and three were nutritional dermatoses. Infectious dermatoses were seen in 346 (50.73%), noninfectious in 253 (37.10%), and nutritional deficiency dermatoses in 83 (12.17%) children. The top three conditions, i.e.. pediculosis capitis (21%), scabies (11%), and bacterial infections (8.52%) contributed 40.52% of the total burden of skin diseases. Conclusion: The prevalence of skin disorders, especially infectious dermatoses, was high among the school children in our study area which is a reflection of the prevalence in the overall population of that area. It is mainly attributed to a lack of proper hygienic measures and health awareness which has to be addressed promptly for the improvement of that area.